Agile Governance Dinas Kesehatan Kabupaten Tulungagung Dalam Menangani Covid-19 - Winda Kusumawati; Arimurti Kriswibowo (Mahesa Research Center, 2021)
Entering November 2020, the Covid-19 case in Tulungagung Regency has spiked, accompanied by a soaring death rate. The concept of Agile Governance is a way to organize better governance by paying attention to the principles in it consisting of a value proposition and agility shift, the character of a leader who is ready for change, a citizen centric approach, and human resource investment. This research is interesting to study because researchers want to know the quick response made by the Tulungagung District Health Office to unexpected changes in meeting the demands and needs of the community due to the Covid-19 pandemic. This research uses qualitative research methods with a descriptive approach. In this study using primary and secondary data. As for the primary data source in this study were Mr. Didik Eka S.P., S.Km., M.Si. as Head of the P2P Division of the Tulungagung Regency Health Office and other related parties and obtained through interviews. Then the secondary data sources, namely documentation and questionnaires, literature, articles, journals, and sites on the internet relating to the research conducted. The results of this study are that the Tulungagung District Health Office responds quickly to the handling of COVID-19 and can run by applying the concept of Agile Governance.